Comparative Views on the Global Energy Problem in the Oil and Gas Pattern - Ramiz, Isgandarov; Ilham, Aslanzade; Mehpara, Orujova; Zaur, Asadov; Aydan, Hadiyeva (Journal of Ecohumanism, 2024)
The article puts forward views on the global energy problem. It focuses on population growth, industry, energy, consumption, exhaustible and inexhaustible resources. Energy has become an indispensable element of social and economic life due to its early use in lighting and heating, and since the early twentieth century in industry and other fields. It is considered that the causes of the global energy problem are related to the rapid growth of the world's population, the growth and development of industrial production. The implementation of these is considered to lead to the efficient use of energy resources, both globally and domestically. There is a need to make certain changes in people's lifestyles, conserve natural resources and increase the use of alternative energy sources. Against the background of a 7-fold increase in the world's population, the growing demand for energy resources of people and society as a whole is a topical issue. The main purpose of the study is to increase attention to the problem of energy in the world, to make certain changes in people's lifestyles and to make sound proposals on alternative energy resources. From a global point of view, the trends in the modern development of energy and the suggestion of more efficient ways of using energy are the scientific novelty of the research. Specifically, in many countries, oil comes out at a depth of 5,000 m and more, instead of the previous 500-1000 m, which has a negative impact not only on society, but also on the environment.